Microstructural characteristics of laser-treated Ni-Cr alloy via low power CO2 laser - GIOVANNI LUSOM, ANAK ANDREW; Dayang Salyani, Abang Mahmod; Khairul Fikri, Tamrin; Amir Azam, Khan; Pierre, Barroy (AIP Publishing, 2025)
Low laser surface treatment has barely been investigated on Ni-Cr alloy, particularly on improving morphological structures. Hence, a study on the impact of low power laser treatment on Ni-Cr alloy was presented in this paper. An attempt to densify the Ni-Cr alloy via low laser power might lead to the enhancement of mechanical properties. The strength of a normal metal composite can be reduced over time due to exposure to extreme heat and impulsive external forces. This will cause alterations to the atomic structure of the composite, and it will lead to changes in its physical and mechanical properties. The irradiation of the CO2 laser aimed to densify the microstructures of the alloy by melting the surface of the composite. The alloy composites were prepared by mixing Ni powders with 20 wt.% of Cr powders and pelletizing them before sintering at 1400 °C. The laser treatment was conducted with the variation of three different magnitudes of low laser power of 10, 20, and 30 Watt, respectively, by keeping the speed of the laser constant at 10 mm/s. The observation was made using Scanning Electron Microscopy (SEM). The significant results displayed that the surface of the alloy was visibly densified after laser irradiation. Currently, it foresees the possibility of a low-power CO2 laser being potentially employed to enhance the morphological structure of an alloy that might lead to obtaining complex structural parts using this alloy.